Stereoselective (4 + 3) cycloadditions of allenyl ethers-furans by chiral auxiliaries inducing and evaluation of anti-breast cancer activity - Lei, Wenli; Song, Yuyang; Long, Ai; Que, Yanyan; He, Shuzhong; Zhong, Hang; Chen, Yang (Frontiers in Plant Science, 2022)
The stereoselectivities and regioselectivities of the (4 + 3) cycloadditions between allenyl ethers with furans induced by chiral auxiliaries are described. A chiral auxiliary was introduced into the substrate allene to gain allenyl ethers, and a (4 + 3) cycloaddition reaction occurs with different substituted furans, showing stereospecificity and regiospecificity. Significantly, the chiral auxiliary can be easily removed under acidic conditions to provide an optical seven-membered carbocycles with oxygen substitution. The antiproliferative activities of these novel cycloadducts was evaluated, and displayed moderate antiproliferative effects towards T47D cells.